SISTEM PENDUKUNG KEPUTUSAN PENITIPAN HEWAN PADA PETSHOP PETSHOP PETSHOP XYZ MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Waty Hutajulu, Bertha Meyke; Irawan, Ari; Tri Habibie, Muhammad (J-ENSITEC, 2023)
This research aims to determine the level of customer satisfaction with the services provided at Petshop XYZ animal care using the Simple Additive Weighting (SAW) method. The research methodology used in the data processing system is data collection techniques such as observation and interviews. The research results illustrate the need for effective management of factors such as facilities, cleanliness, service and price to ensure a positive experience for customers.